Pola Asuh Demokratis, Kepercayaan Diri dan Kemandirian Mahasiswa Baru - Asiyah, Nur (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract. The purpose of this research was to examine the relation between democratic-parenting and self confidence with independent new college student. The subject of the study were 131 newÂ college student of faculty preaching the state islamic institute sunan ampel surabaya. Data were collected by scale of democratic-parenting, self confidence and independent scale. The data analysis used multiple regression analysis showed that the democratic-parenting anda self confidence have a significant relation with independent newÂ college student. The result of correlation analysis between either democratic-parenting or self confidence with independent showed a positive correlation signifycantly. Variables of democratic parenting and self confidence give effecttive contribution toward independent new college student about 51,3%.Key words : Democratic-Parenting, Self Confidence, Independent New College Student.